INCREASING MICROGRID CONTROLLING SYSTEM AND SAFETY BY USING ARTIFICIAL INTELLIGENCE - Mamadaliyev, Musulmonkul Imomali ugli; Soliyev , Bobonazar Gulomjon ugli (Educational Research in Universal Sciences, 2023)
As the demand for reliable and resilient energy sources continues to rise, microgrids have emerged as a promising solution for localized power generation and distribution. This article explores the integration of artificial intelligence (AI) into microgrid control systems to bolster their efficiency, responsiveness, and safety. The traditional approaches to microgrid control often face challenges in adapting to dynamic and diverse energy landscapes. By harnessing the capabilities of AI, we can optimize the operation of microgrids by intelligently predicting, managing, and responding to fluctuations in energy production and consumption.